Evaluating and Enhancing In-Service Mathematics Education: Insights, Recommendations, and Program Transformation - Meenakshi, P.K.; Madhu, B.; Vidhya, K.N. (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
The study presented in this research paper investigates the effectiveness of a training program designed to enhance the teaching of Mathematics knowledge and skills in a specific subject of Mathematics. The research employs a comparative analysis of pre-test and post-test results to assess the impact of the training program on participant performance. The pre-test data, collected before the training, provides a baseline measurement of participants’ initial knowledge and skills. Subsequently, participants undergo the training program, which is designed to address identified learning objectives. After the training, a post-test is administered to evaluate the participants’ knowledge and skills. The study analyzes the changes in average scores between the pre-test and post-test to determine the program’s effectiveness. The results indicate a significant improvement in participants’ performance from the pre-test to the post-test, suggesting that the training program had a positive impact on their knowledge or skills related to the teaching of Mathematics. While the study observes slight variations between genders in the pre-test, these differences remain consistent in the post-test. The findings highlight the potential of the training program to enhance participant proficiency and emphasize the importance of ongoing improvement and adaptation to meet evolving learning needs. The study concludes by discussing potential future directions for the program, including the development of advanced modules, specialized tracks, and a blended learning approach. Additionally, it underscores the significance of continuous assessment, practical application, and long-term impact evaluation. Overall, the research underscores the value of effective training programs in promoting knowledge acquisition and skill development.